A new approach of H∞ filtering for combustion systems using optical instrumentation. (January 2022) - Palma, Jonathan M.; Morais, Cecília F.; Garcés, Hugo O.; Carvalho, Leonardo de P.; Oliveira, Ricardo C.L.F.
Abstract: This paper proposes a new filtering scheme applied to a linearized model of a nonlinear representation for combustion systems, whose parameters are obtained by means of optical sensors. To ensure a robust representation regarding the chosen operation point and external disturbances variations, a linear parameter-varying (LPV) state-space representation is proposed in terms of noise disturbances and time-varying parameters affecting the plant (like the instrumentation noise and non-laminar air flow). Concerning the proposed filtering scheme, a new observer structure, which includes the incorporation of the control signal as an additional input of the filter, is proposed to assure improved stability margins and performance given in terms of the H ∞  norm. The filter design method is based on a convex optimization technique and is capable to deal with unstable dynamics. A numerical experiment, whose data were obtained from an actual combustion plant, illustrates the flexibility and advantages of the method when compared with the maximum correntropy criterion based Kalman filter, the full-order filter and the standard Luenberger observer. Highlights: Linear parameter-varying (LPV) model for combustion systems identified by optical instrumentation. Time-varying parameters represent the non-laminar air flow and instrumentation noise. New observer structure for the filter, incorporating the control signal as additional input. A new H ∞  filter design condition formulated in terms of linear matrix inequalities. Proposed filter provides better performance than other methods from the literature.